SERVICE RECOVERY, CUSTOMER SATISFACTION AND CUSTOMER LOYALTY: EVIDENCE FROM INDONESIA’S HOTEL INDUSTRY - Apivah, Devina; Hertina, Dede; Abd Razak, Anis (International Journal of Psychosocial Rehabilitation, 2020)
This objective of this study is to examine the relationship between service recovery towards customer loyalty in the hotel industries. Role of customer satisfaction is also measured as a control variable in between service recovery and customer loyalty. This study is used a quantitative method thus it uses a questionnaire survey form to collect data from respondents. This study used a convenience sampling technique where data were collected and administered by the respondents who visited the selected hotel during specific time at various days in a month that being selected. In total the data collections took 10 days to complete. A total of 300 questionnaires were distributed and 145 were returned (48 percent response rate). Data analysis were done using the structural equation modelling. The results indicate that service recovery does influences customer satisfaction and customer loyalty. It also recorded that customer satisfaction play a vital role towards customer loyalty rather than a direct relationship between service recovery towards customer loyalty. Hotel industries should have focused on handling service recoveries in order to avoid customers’ frustration and negative customer experiences.